Reproduction and Production Performance of Swamp Buffalo (Bubalus bubalis) at the Small-Scale Holder Farmer in Sragen Regency, Central Java, Indonesia - Nimas Alifia Nastiti; Joko Riyanto; Ratih Dewanti; Muhammad Cahyadi; Ari Kusuma Wati; Wari Pawestri; Yuli Yanti (Jurnal Sain Peternakan Indonesia, 2023)
This research aimed to determine the performance of swamp buffalo reproduction and production at the small-scale holder farmer in Sragen Regency, Central Java, Indonesia, from June to September 2021. The method used in this research was a survey with a census (complete) sample determination. Data collection applies to interviews, observations and literature studies. Research parameters used in reproductive performance were calving interval (CI), service per conception (S/C), age of the first estrus, age of first birth and postpartum estrus. In contrast, production performance parameters were chest circumference, body length and estimated body weight. The result of research on reproductive performance showed that the average CI were 13.2±0.9 months, S/C 1.25±0.4 time, age of first estrus 2.7±0.6 years, age of first birth 3.7±0.5 years and postpartum estrus were 30–60 days. The result of research on the production of male buffalo body length was 205.3±1.7, and the body length of female buffalo was 127.2±4.3 cm, whereas the chest circumference of female was 205.3±1.7 cm and the chest circumference of the male was 189±2.8 cm. The estimated body weight of females and males were 516.7±7.7 kg and 445.2±11.9 kg. Based on the result of the research, the characteristics of swamp buffalo reproduction and production in Sragen Regency were classified as good.